EARLY MEDIEVAL ROCK-CUT BURIALS OF AGARAK - Engibaran, Nora; Miridzanan, Dianna; Ter-Minasan, Lilit; Hudaverdan, Anait (History, Archeology and Ethnography of the Caucasus, 2025)
This study presents the initial findings from the archaeological and anthropological analysis of rock-cut burials discovered at the Agarak necropolis. Situated in the Aragatsotn Province of the Republic of Armenia, between the villages of Agarak and Voskehat, the Agarak archaeological site features a northern rock platform where excavations have revealed seven occupational layers spanning the Early Bronze Age to the Late Middle Ages. Within the eastern sector of this platform, twenty-one burial pits, dating to the early medieval period, were identified. These unlined pits, oriented east-west and arranged in four irregular rows, were cut into the tuff bedrock. Some still contain skeletons or bones. One trapezoidal pit exhibited stepped edges to support a lid, while others displayed a distinctive anthropomorphic design, being wider and shallower at the western (shoulder) end and gradually narrowing towards the east (legs). Rock-cut burial pits have a documented presence in the Armenian Highlands since the Early Bronze Age, with known parallels at sites such as Metsamor and Pijut. Beyond Agarak, where they are most prevalent, early medieval examples have also been documented at Metsamor, Metsadzor, the Yerevan Botanical Garden, and in Artsakh. The investigation of these burials involved an evaluation of the preservation status and completeness of the skeletal remains. Age-at-death estimations were conducted using indicators such as ossification and dental eruption in individuals under 23 years, and diaphyseal length of long bones. For older individuals, biological age was assessed through analysis of cranial suture closure, dental wear, joint and symphyseal degeneration, and the presence of degenerative-dystrophic changes on vertebral bodies.